The Camperdown Program: Outcomes of a New Prolonged-Speech Treatment Model. - O'Brian, Sue; Onslow, mark; Cream, Angela (Journal of Speech, Language & Hearing Research, 2003)
Considerable research has been directed at the outcomes of prolonged-speech (PS) treatment for the control of chronic stuttering, but little research to date has focused on the PS treatment process. This report examines a Stage 2 clinical trial of a reconceptualized PS treatment model known as the Camperdown Program. This program requires fewer clinician hours than traditional programs and has no formal transfer phase. Additionally, it incorporates the following treatment process innovations, which replace treatment process components that are intuitively and empirically problematic: (a) PS is taught without incorporating target behaviors in clinician instruction, (b) participants learn to control stuttering without programmed instruction, and (c) the treatment process does not involve clinician identification of stuttering moments. Thirty participants were initially enrolled in the trial. Final outcome data are presented for the 16 participants who completed all trial requirements, including 12 months posttreatment data collection. These 16 participants showed minimal or no stuttering in everyday speaking situations for up to 12 months after entering the maintenance program, with speech rates in the normal range. Speech naturalness and social validation data were also favorable. Although self-report data generally confirmed the speech data, the results were not as positive. The present outcomes were achieved in a mean of 20 hours of clinic attendance per participant, which is much fewer than the hours required by treatment programs reported recently that run intensively over 2-3 weeks. The promise of this Stage 2 clinical trial has led the authors to initiate a Stage 3 randomized controlled trial of the Camperdown Program. Reprinted by permission of the publisher.